SOME FIXED-POINT RESULTS FOR ASYMPTOTICALLY REGULAR MAPS IN N-FUZZYb-METRIC SPACE - Happy Hooda,Archana Malik,Manish Vats (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this paper, we define N-fuzzy b-metric space and then weinvestigate fixed point results on the structure of N-fuzzy b-metric space using asymptotically regular map and asymptotically regular sequence. These theorems generalize and improve some known fixedpoint theorems in literature.